Analysis of the Manufacturing Process of Shredded Tuna Products in UMKM Citra Permata Kendari - Lesmana, Sakinah Ambang Diandry; Herdhiansyah, Dhian; Syukri, Muhammad; Asriani, Asriani (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This study aims to analyze the process of making shredded tuna products at UMKN Citra Permata Kendari. The research conducted is a case study). The analysis in this study uses descriptive analysis. The results of this study indicate that the process of making shredded tuna at UMKM Citra Permata Kendari goes through various stages of the production process, including cleaning tuna to be used as shredded fish, steaming sliced tuna to make it easier to take the meat and separate it from the bones. Fish, seasoning to give a unique taste to the shredded tuna, frying until the color of the shredded tuna turns brown, pressing to remove the remaining oil on the shredded tuna, and packaging for the final production stage of shredded tuna products.